PEMILIHAN MODEL MANAJEMEN PROYEK ERP HYBRID MENGGUNAKAN MULTI CRITERIA DECISION ANALYSIS (MCDA) - Rusydah, Nafisa Devi Nur; Rohmatillah, Roji; Yaqin, Muhammad Ainul (AnoaTIK: Jurnal Teknologi Informasi dan Komputer, 2026)
The selection of an Enterprise Resource Planning (ERP) project management model is crucial because ERP implementations have a high level of complexity and risk of failure. However, the process of selecting a project management methodology is still often carried out based on organizational preferences without considering specific project characteristics. This study aims to develop an adaptive selection model based on project characteristics to determine the most appropriate ERP project management methodology. The method used is Multi-Criteria Decision Analysis (MCDA) which integrates Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) using a scenario-based weighting approach. Simulations were conducted using the Project Management Risk Raw Dataset consisting of 4000 simulated project data with six main criteria, namely requirement stability, system complexity, Agile readiness, risk, documentation, and stakeholder involvement. The results show that the Hybrid B model (Agile iterations with formal governance) is the most dominant model with a recommendation rate of 47.45%, followed by Agile at 45.53%, while other alternatives show lower recommendation rates. These results indicate that the hybrid approach is more adaptive to be applied to modern, dynamic ERP projects.